Perancangan Antena Mimo Array 37 GHZ Untuk Jaringan Komunikasi 5G - Sholeh, Mohamad; Rahayu, Yusnita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The development of communication technology was started from first generation (1G) to fourth generation (4G), which each new generation always comes with a significant increase in performance. With the increasing of wireless mobile devices and services in the future, there are still some problems and challenges that can not be accommodated even by 4G, such as high data rates, area coverage, and low energy consumption. The 5G (Five Generation) technology presents to solve problems and the need to improve network efficiency and capacity, improved data rate with better coverage at lower power consumption. This research will design a planar array microstrip antenna, MIMO (Multiple Input Multiple Output) 2x2, which works at a frequency of 37 GHz using CST (Computer Simulation Technology) Microwave Studio software. The antenna was designed by using RT-duroid 5880 substrate with a thickness of 0.508 mm. This design uses the technique of Microstrip Line/T-junction consisting of 4 elements. The simulation results obtained for 4 elements array are the return loss of -28.483 dB, the bandwidth of 2,12 GHz, VSWR (Voltage Standing Wave Ratio) ≤ 1,078 and gain ≥ 11,8 dBi, The results obtained by MIMO 2x2 antenna are the return loss of -26,767 dB, the bandwidth of 2,12 GHz, VSWR ≤ 1,096 and gain ≥ 18,7 dBi. Keywords: Return loss, bandwidth, VSWR, gain